Asymmetry of spinal segments mobility in canoeists and its relationship with racing speed - Rynkiewicz, M.; Rynkiewicz, T.; Starosta, W. (Journal of Human Kinetics, 2013)
The aim of this study was to determine the extent of asymmetry of spinal segment mobility in canoeists. Moreover, the relationship between this parameter and racing speed was analyzed. The study included 18 canoeists with a mean age of 16.4 years. Mobility of cervical, thoracic and lumbar spine, in sagittal, coronal and transverse planes, was measured with the aid of a tensometric electrogoniometer. The racing speed was based on results achieved during the qualifying competition for the Polish national team. Spinal mobility was measured within two days after the competition. Significant associations were observed between average racing speed and the asymmetry coefficients of the cervical (r=-0.52; p=0.03) and lumbar spinal flexure in the coronal plane (r=0.57; p=0.01). The extent of the asymmetry of the cervical spine flexure in the coronal plane should possibly be reduced, because such asymmetry exerts a negative effect on racing speed. In contrast, canoeist`s training should be oriented towards increasing the asymmetry of the lumbar spine flexure in the coronal plane. However, one should keep in mind that such an approach, although favorable in terms of race performance, could negatively affect the canoeist`s health.